Renal Implications of Dysregulated Protein Homeostasis: Insights into Ubiquitin–Proteasome and Autophagy Systems - Charlotte Delrue; Marijn M. Speeckaert (Biomolecules)
The ubiquitin–proteasome system (UPS) and autophagy maintain protein homeostasis, which is critical to cellular function and survival. The dysregulation of these pathways has been recognized as a hallmark of acute kidney injury and chronic kidney disease. This review elucidates the role of the UPS and autophagy in kidney disease, namely through inflammation, oxidative stress, fibrosis and apoptosis. The pathways of NF-κB, TGF-β and mitochondrial failure result in glomerular injury and tubulointerstitial fibrosis due to impaired proteostasis in podocytes and tubular epithelial cells. Recent studies have revealed a connection between the autophagic process and the UPS, wherein compensatory mechanisms aim to spike down proteotoxic stress but eventually seem inadequate in cases of chronic derangement. Low-dose pharmacological inhibitors, autophagy modulators, and new gene and nanotechnology-based treatments may all help to restore the protein balance and reduce kidney injury. A more thorough understanding of these pathways is needed to develop kidney-protective and disease-modifying therapeutic interventions.